Exploration of and insights into advanced topical nanocarrier systems for the treatment of psoriasis - Zhang, Miao; Hong, Seokgyeong; Sun, Xiaoying; Zhou, Yaqiong; Luo, Ying; Liu, Liu; Wang, Jiao; Wang, Chunxiao; Lin, Naixuan; Li, Xin (Frontiers in Medicine, 2022)
Psoriasis is a chronic inflammatory skin disease with an underlying autoimmune pathogenesis that has brought great distress to patients. Current treatment options include topical therapy, systemic therapy, and phototherapy. By disrupting the stratum corneum, nanocarriers have unique advantages in allowing drug carriers to be tailored to achieve targeted drug delivery, improve efficacy, and minimize adverse effects. Furthermore, despite their limited success in market translatability, nanocarriers have been extensively studied for psoriasis, owing to their excellent preclinical results. As topical formulations are the first line of treatment, utilize the safest route, and facilitate a targeted approach, this study, we specifically describes the management of psoriasis using topical agents in conjunction with novel drug delivery systems. The characteristics, advantages, weaknesses, and mechanisms of individual nanocarriers, when applied as topical anti-psoriatic agents, were reviewed to distinguish each nanocarrier.